Assessment of Neuroinflammatory Markers (IL-6, TNF-α) and Cognitive Decline in Early Alzheimer’s Disease Patients - BIBI, FEHMIDA; ULLAH, IKRAM; NASEER, MUHAMMAD IMRAN (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Alzheimer disease is a progressive neurodegenerative disorder characterized by premature deterioration of the brain and progressive memory impairment. Emerging evidence suggests that neuroinflammation plays a central role in the pathogenesis of the disease, with pro-inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) contributing to neuronal dysfunction and cognitive decline. Objective: To measure serum IL-6 and TNF-α levels in patients with early-stage Alzheimer disease and to determine their association with cognitive deterioration. Methods: This cross-sectional comparative study was conducted at a tertiary care hospital from March 2023 to February 2025. A total of 70 participants were enrolled, including 40 patients with early Alzheimer disease and 30 cognitively healthy controls. Cognitive performance was assessed using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). Serum IL-6 and TNF-α levels were measured using enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using SPSS version 26, and correlations were assessed using Pearson’s correlation coefficient. Results: Patients with early Alzheimer disease had significantly lower cognitive scores than controls (MMSE: 21.48 ± 2.86 vs 28.27 ± 1.41; MoCA: 18.94 ± 3.17 vs 26.31 ± 1.84; p = 0.001). Serum IL-6 and TNF-α levels were significantly elevated in the Alzheimer group (IL-6: 8.61 ± 2.49 pg/mL vs 4.29 ± 1.47 pg/mL; TNF-α: 14.87 ± 4.12 pg/mL vs 8.64 ± 2.31 pg/mL; p < 0.001). Both cytokines demonstrated significant negative correlations with MMSE and MoCA scores, indicating that higher inflammatory marker levels were associated with poorer cognitive performance. Conclusion: Elevated serum IL-6 and TNF-α levels in early Alzheimer disease are significantly associated with cognitive decline. These findings support the role of neuroinflammation in Alzheimer disease progression and suggest that these inflammatory markers may serve as accessible biomarkers for early disease monitoring and prognostic evaluation.